The many faces of tissue factor - MACKMAN, N. (2009)
Tissue factor (TF) is a member of the cytokine receptor superfamily and binds FVII/VIIa. The TF:FVIIa complex has both procoagulant and signaling activities. It functions in many biological processes, including hemostasis, thrombosis, inflammation, angiogenesis and tumor growth. Importantly, TF is essential for hemostasis. However, increased TF expression within atherosclerotic plaques and elevated levels of circulating TF-positive micro particles promote thrombosis. TF increases inflammation by enhancing intravascular fibrin deposition, by increasing the formation of pro-inflammatory fragments of fibrin and by generating coagulation proteases, including FVIIa, FXa and thrombin, that activate protease-activated receptors (PARs). In endotoxemia and sepsis, TF-dependent thrombin generation and activation of PAR1 on dendritic cells enhance inflammation. Finally, the TF:FVIIa complex contributes to tumor growth by activating PAR2.